Differential Expression of Chemokines, Chemokine Receptors and Proteinases by Foreign Body Giant Cells (FBGCs) and Osteoclasts. Issue 7 (July 2014) - Khan, Usman A.; Hashimi, Saeed M.; Khan, Shershah; Quan, Jingjing; Bakr, Mahmoud M.; Forwood, Mark R.; Morrison, Nigel M.
Abstract Osteoclasts and foreign body giant cells (FBGCs) are both derived from the fusion of macropahges. These cells are seen in close proximity during foreign body reactions, therefore it was assumed that they might interact with each other. The aim was to identify important genes that are expressed by osteoclasts and FBGCs which can be used to understand peri‐implantitis and predict the relationship of these cells during foreign body reactions. Bone marrow macrophages (BMM) were treated with receptor activator of nuclear factor kappa B ligand (RANKL) to produce osteoclasts. Quantitative PCR (qPCR) was used to identify the genes that were expressed by osteoclasts and FBGCs compared to macrophage controls. TRAP staining was used to visualise the cells while gelatine zymography and western blots were used for protein expression. Tartrate‐resistant acid phosphatase (TRAP), matrix metallo proteinase 9 (MMP9), nuclear factor of activated T cells 1 (NFATc1), cathepsin K (CTSK) and RANK were significantly lower in FBGCs compared to osteoclasts. Inflammation specific chemokines such as monocyte chemotactic protein (MCP1 also called CCL2), macrophage inflammatory protein 1 alpha (MIP1α), MIP1β and MIP1γ, and their receptors CCR1, CCR3 and CCR5, were highly expressed by FBGCs. FBGCs were negative for osteoclast specific markers (RANK, NFATc1, CTSK). FBGCs expressed chemokines such as CCL2, 3, 5 and 9 while osteoclasts expressed the receptors for these chemokines i.e. CCR1, 2 and 3. Our findings show that osteoclast specific genes are not expressed by FBGCs and that FBGCs interact with osteoclasts during foreign body reaction through chemokines. J. Cell. Biochem. 115: 1290–1298, 2014. © 2014 Wiley Periodicals, Inc.